EFFECT OF pH, SELECTED CYCLODEXTRINS AND COMPLEXATION METHODS ON THE SOLUBILITY OF LORNOXICAM - Patil, Shrishailgouda S.; Gupta, V. Ram Mohan; Gupta, K. Srikanth; Doddayya, H. (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: The objective of the present study is to investigate the effect of pH, selected cyclodextrins and methods of complexation on the solubility of lornoxicam. Methods: Phase solubility studies were carried out according to Higuchi and Connors. Inclusion complexes of lornoxicam were prepared by different methods like kneading, ultrasoncation, spray drying along with the physical mixtures using Î² cyclodextrin and hydroxypropyl Î² cyclodextrins. Results: Lornoxicam being weakly acidic drug showed extremely low solubility in the acidic medium (pH 1.2) and poor solubility in water. The solubility of the drug increased as the pH of the medium was subsequently increased up to 7.4 and a drastic increase in solubility perhaps several hundred folds was observed with the alkaline phosphate buffer (pH 10.0). Phase solubility studies revealed that, hydroxypropyl Î² cyclodextrin (HP Î² CD) up to the concentration of 20 mM showed a linear increase in solubility of lornoxicam whereas the solubility of lornoxicam was increased up to Î² cyclodextrin (Î² CD) concentration of 14 mM and beyond that the solubility of the drug reduced probably due to precipitation of the complexes. The stability constant (Ks) was found to be 378.55 M-1 and 867.262 M-1 for Î² CD and HP Î² CD respectively. Inclusion complexes of lornoxicam with cyclodextrins were prepared employing different methods and the effect of complexation methods on the dissolution of lornoxicam was studied. Dissolution studies revealed that, irrespective of the cyclodextrins used (Î² CD and HP Î² CD), highest drug release rate was observed from the spray dried products compared to those prepared by kneading and ultrasonication methods. Inclusion complexes prepared using HP Î² CD showed higher drug release compared to those prepared using Î² CD. Conclusion: The study demonstrated the distinctive pH dependent of solubility of lornoxicam and also showed that cyclodextrins especially HP Î² CD can be utilized to improve the solubility of lornoxicam.